the Study of Information Process, Control and Learning in Multinational and Transactional Organization - manijeh bahrainizadeh (مطالعات مدیریت بهبود و تحول, 2004)
The international and transnational  organizations are the most complex organizations  that need especial  mechanism  of control and management.  In these  organizations  regarding  the international structure  and  global environment,  communication   between   units  that  are  speard  around   the world, require  different informational processing  methods. Control  in these organization   are  very   complex   because   of cultural  diversity   in  global environment.  Thay need to create competitive  innovation for theire  survival in   the   global   competitive    environment    and   thay   must   be   learning organizations.  Through  learning,  the units  and subsiders  exchange  science and knowledge and result in synergy and the speared of new science. In  resent  decades  the  study  of these  organizations  has  obtained  a special position  in organization  study and every  scholar  regard to his  interest and experience    uses   different   social   and   economical   theories   to   explain functional  and  structural  dimensions  of this  organizations.  In  this  article communication,  control,  learning and information .process in these organizations  are discussed. To analyzing, the following theories are uses: The institutional theory. The economic organization theory